Cooperative Learning Design of Number Head Together in Indonesian Lesson Class 6 - Agus Suryana; Malika Nurul Audina (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2022)
The development of number head together cooperative learning model was developed to make it easier for teachers to assist students in understanding Indonesian lesson for class 6 in incident material and to improve concentration and for improve students' concentration and learning outcomes. The writing of this article is for: Explain the application of the design of learning cooperative learning type numbered heads together, explains the advantages of Learning model type numbered heads together, describes the steps of learning kooperative learning type head benomor on the lessons Indonesian class 6 material incidents. Methods this study uses the method of literature by analyzing a variety of books and journals related to the application of learning kooperative learning numbered heads. The results of the inference to conclude that : the design of learning kooperative learning numbered heads is one of the cooperative learning model that aims to develop cooperation,facilitate the division of tasks as well as the students learn to carry out the responsibilities of individuals as members of groups. The advantages among others : to improve the achievement of student learning, train the responsibility of the student, help students in learning, improve students ' confidence, develop a sense of belonging and cooperation, eliminate the gap between that smart is not smart. Learning steps kooperative learning numbered heads in Indonesian subjects as follows : first of all, in preparation, then students are divided into groups. after the division of the group, namely the assignment given to each student according to the number, then the educator requires each group has a book of the package as well as a guide book, after which students conduct a discussion about a problem or a question that has been given. After all is done, then educators provide a conclusion to the students of material covered. Keywords: Design, Cooperative Learning, Number Head Together, Indonesian Lesson.